Epigenetic aspects of chronic diseases - Roach, Helmtrud I.; Bronner, Felix; Oreffo, Richard O.C (Springer-Verlag London Limited, 2011)
Epigenetic Aspects of Chronic Diseases assembles in comprehensive form what is known about the role of epigenetics in chronic disease development. This book provides new insights into treatment, including modulation of epigenetic regulation. Each chapter gives an outline of a respective disease, explains why epigenetics may be involved in the disease process and then presents the evidence of how changes in epigenetic status contribute to initiation and progress of the disease. The final chapters look towards future therapeutic treatment, based on manipulation of epigenetic aspects. Written by widely published experts, Epigenetic Aspects of Chronic Diseases is a valuable reference tool for clinicians and researchers who investigate and treat chronic diseases, as well as health care personnel, post-doctoral fellows and medical or dental students.